Oxford urdu silsila " koonj" - Amna azafar (Oxford University Press Karachi, 1999)
"Oxford Urdu Silsila Koonj" by Amna Azfar is a captivating collection of Urdu poetry that explores themes of love, loss, and introspection, beautifully woven into evocative verses that resonate with deep emotional expression.